ОРГАНІЗАЦІЯ ПІЗНАВАЛЬНОЇ ДІЯЛЬНОСТІ УЧНІВ У ТЕОРІЇ ТА ПРАКТИЦІ ТРУДОВОГО НАВЧАННЯ (Педагогіка вищої та середньої школи, 2008)
In the article an author specifies the concepts of activity, cognitive activity, describe the essence of the problem of organization the cognitive activity on the labour teaching lessens.